Offshore Detention in Australia: Behrouz Boochani’s No Friend but the Mountains: Writing from Manus Prison (2018) - Janet M. Wilson (Institute of English Studies, 2021)
This article focuses on the “Pacific Solution,” the Australian national policy of controlling illegal migration by detaining refugees in Immigrant Detention Centres in offshore Pacific islands of Manus and Nauru, and the human rights issues it raises. It refers to Behrouz Boochani’s prize-winning refugee memoir, No Friend but the Moun- tains: Writing from Manus Prison (2018) as both a prison narrative of resilience and a politically resistant text, and it discusses Boochani’s representation of Manus Detention camp as “The Kyriarchal System” in terms of Foucault’s “monstrous heterotopia.” The ar- ticle emphasises the issues of accountability and responsibility in the bilateral governance arrangements of the Manus Detention Centre between Australia and Papua New Guinea, and considers the possibility of more humane detention practices in the future.